Demonetisasi Allah melalui Sebuah Ekoteologi Pasifik terkait Kehidupan,Istirahat, dan Pembatasan - Aiava, Faafetai (Indonesian Journal of Theology, 2025)
This article explores how the commodification of time and theology under the global cash economy has contributed to ecological and spiritual disconnection in the Pacific. It interrogates what happens when God is shaped by market logic, becoming a transactional figure aligned with material prosperity rather than the flourishing of all life. Rather than drawing from stewardship models, it proposes a divine economy that honors Earth’s rhythms, embraces Pacific wisdom and values, and upholds the whole of life as sacred. To “demonetize” God, then, is not merely to critique capitalism, but to recover a theological vision in which rest, restraint, and kinship with all life point toward ecological justice